Renal Artery Dimensions and Variation on Computed Tomography Angiogram: A Cross-sectional Study. (Med Phoenix, 2022)
IntroductionA knowledge of renal artery dimension is necessary for characterizing the physiological change as well as pathological process undergoing in the renal artery likely stenosis, ectasia, or aneurysm. This study aims to explore the anatomy of the renal artery with regards to its dimension, relation, and branching and identify the common anatomical variation.Materials and MethodsThe study was a retrospective hospital record-based study conducted during the period of one year from 2019 January to 2019 December. All abdominal CT angiograms were reviewed for renal artery anatomy and variation. Abnormal Abdominal CT angiograms were excluded from the study. Normal anatomy, dimensions, and variation of renal vasculature were assessed.ResultsA total of 110 patients included the inclusion criteria and was included in the study. The renal length and size of the renal artery were significantly larger on the left side. The renal artery diameter showed positive correlation with renal length (r= 0.432; p